Non-Traditional Learning - Torvi, Sudhanshu Prasad; Mithun Krishna, B. K.; Murthy, Madhav (Journal of Engineering Education Transformations, 2025)
Learning is an essential part of every individual’s life as it helps one to increase their knowledge and also to enhance skills. The interactions, observations, experiences in one’s daily routine also contribute to his learning. Every individual should also make conscious efforts to learn new things. This paper talks about a few nontraditional learning methods like MOOC’s, social learning and open ended experimentation to be incorporated into the curriculum in addition to conventional teaching learning process. A survey was conducted among the students from different colleges. The study indicates that the awareness of MOOCs, Outcome Based Education and Social learning is high among students though the level up-to which they’re aware is limited. The interpretation of the survey highlights the students’ inclination towards sources other than just a classroom to learn.